The effect of the irrigant activation protocol on postoperative pain in maxillary incisors with asymptomatic apical periodontitis: A three‐arm randomized clinical trial - Mohammad Tamer Abbara; Samar Akil; Omer Hamadah; Hassan Achour; Ghina Mahayni; Yasser Alsayed Tolibah (Wiley, 2023)
Abstract Objectives This study aimed to compare the effects of three irrigation activation systems (IAS) on postoperative pain (PP) in activating three final irrigants: sodium hypochlorite 5.25%, ethylenediaminetetraacetic acid 17%, and chlorhexidine 2%. Materials and Methods This parallel randomized clinical trial included referred patients with asymptomatic large‐sized apical lesion incisors. A standard method was followed in the canal cleaning and shaping for all included patients in the study. Then, the patients were randomly assigned (1:1 allocation) into three groups: G1 (n = 20) with passive ultrasonic irrigation activation; G2 (n = 20) with XP‐Endo Finisher file activation; and G3 (n = 20) with diode laser (810 nm) activation. PP was estimated in all groups using a visual analog scale after 1, 3, 7, and 14 days of treatment. Comparisons between the groups were made using the Kruskal−Wallis test, whereas the Mann−Whitney U test was used in the pairwise comparisons. Results Sixty patients were followed‐up in this trial. There were significant differences between the groups in terms of PP After 1, 3, and 7 days of treatment (p = 0.002, p = 0.017, and p = 0.006, respectively). On the first day of treatment, G3 showed the lowest PP compared with G1 and G2 (p = 0.007 and p = 0.001, respectively). On the third day of treatment, G3 showed less PP compared with G2 (p = 0.005). On the seventh day of treatment, G2 showed the highest PP compared with G1 and G3 (p = 0.012 and p = 0.003, respectively). Conclusions The XP‐Endo Finisher file caused the highest PP level especially in the next day and 3 days of the treatment, whereas the diode laser had the lowest PP level during the first week of treatment. It is noteworthy that PP disappeared completely after 2 weeks of treatment with all three IASs. Trial Registration The trial was registered in the ISRCTN registry (Trial ID: SRCTN99457940).